When Should the Majority Rule? Experimental Evidence for Madisonian Judgments in Five Cultures. Issue 1 (29th May 2021) - Bor, Alexander; Mazepus, Honorata; Bokemper, Scott E.; DeScioli, Peter
Abstract: In democracies, majority-rule voting is an esteemed rule for collective decisions, but its hazards have recently become apparent after a series of controversial referendums and ascendant populist leaders. Here, we investigate people's judgments about when voting is appropriate for collective decisions across five countries with diverse cultures and political institutions (Denmark, Hungary, India, Russia, and USA). Participants read scenarios in which individuals with conflicting preferences need to make a collective decision. They judged whether the group should decide by voting, consensus, leadership, or chance. We experimentally manipulated whether the group contains a vulnerable minority – a smaller number of people with more at stake than the majority. In all five countries, participants generally preferred voting without a vulnerable minority, with relatively greater support for voting in more democratic countries. But, when the group included a vulnerable minority, participants in all countries reduced their support for voting and instead preferred consensus.